The Relationship Evaluation between Physical Disabled's Social Support and Life Quality in Raad's Education Centers - Nasrin Khosravi-Tapeh; Ghoncheh Raheb; Maliheh A'rshi; Mostafa Eglima (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: Social protection is one of the most important predictors of people's health. The aim of this study was to determine the relationship between social support and life quality, among disableds of Raad's educational institutes. Materials & Methods: In this cross-correlation research 195 disableds that aged between 18-35 were selected with stratified random sampling method from Raad's institutes proportional to each three centers quota to the total (Alghadir, Shargh and Markazi). Questionnaires of the Vuax social support and the Lancashire life quality were used. To analyze the data, Pearson and Spearman correlation coefficients and regression were used. Results: obtained results revealed a significant relationship between social support subscales (family, friends and other's social support) with Psychological factors (Psychological comfort and self concept) and Social Factors (Social and family relationships) of life quality in handicaps (P<0.01). Conclusion: The results of the present study confirm the importance of social support in the disabled's life quality, therefore it is necessary that the social support considered as a high suppler quality of life, in disabled's health promotion interventions design.